Analysis of the Roles of Glucose Transporter 1 and Hexokinase 2 in the Metabolism of Glucose by Extrahepatic Bile Duct Cancer Cells. (March 2015) - Yoon, Sun Och; Jeon, Tae Joo; Park, Joon Seong; Ryu, Yong Hoon; Lee, Jae-Hoon; Yoo, Jung Sik; Kim, Jae Keun; Yoon, Dong Sup; Oh, Eun Ji
<x xml:space="preserve">Abstract</x> Purpose of the Report Extrahepatic bile duct (EHD) cancer varies in uptake of FDG. The aim of the present study was to determine the role of glucose transporter (GLUT) 1 and hexokinase (HK) 2 in the glucose metabolism of EHD cancer cells using immunohistochemistry and 18F-FDG PET/CT. Methods Twenty-six patients with EHD cancer who underwent baseline PET/CT and surgery were studied. Biopsies were immunohistochemically analyzed using antibodies against GLUT1 and HK2, and the expression was scored from 0 to 4 according to the percentage of stained cells. SUV and tumor-to-liver ratio (T/Lratio) were obtained from 18F-FDG PET/CT data. SUV and T/Lratio and GLUT1 and HK2 expression were compared with histological grades and tumor locations (proximal and distal EHD) to correlate glucose metabolism with the expression of GLUT1 and HK2. Results SUV, T/Lratio, and GLUT1 and HK2 expression did not differ as a function of histological grade and tumor location. GLUT1 and HK2 were expressed in 20 (76.9%) and 22 (84.6%) of 26 tumor biopsies, respectively. The GLUT1 score, SUV, and T/Lratio increased, and the GLUT1 score, but not the HK2 score, correlated significantly with SUV (ρ = 0.648) and T/Lratio (ρ = 0.703). There was no direct correlation between the expression of GLUT1 and that of HK2 (ρ = 0.2046, P = 0.3161). Conclusions Although GLUT1 and HK2 regulate intracellular accumulation of FDG in many cancers, only GLUT1 expression was correlated with FDG uptake by EHD cancers.